Metal foams: A review for mechanical properties under tensile and shear stress - Kalpakoglou, Thomas; Yiatros, Stylianos (Frontiers in Materials, 2022)
Due to their mechanical properties, metal foams are used in various fields. The aim of the present research is to collect different studies about the important mechanical properties of metal foams, such as Young’s modulus, tensile and shear strength, relative density, etc. under tensile and shear loading. Gaps were identified in the methodological embodiments of the experiments due to the use of different standards, as well as in the calculation of mechanical properties through mathematical relations in tensile and shear, which led to deviations between the experimental results and these. Furthermore, this work records sequences and connections between experimental results of different tasks as well as solutions to the aforementioned issues.